Effect of Fatigue on Quality of Life in Pediatric Oncology Patients - Aslı Akdeniz Kudubeş; Murat Bektaş (Journal of Pediatric Research, 2017)
As a result of the medical progress in the field of pediatric oncology, childhood cancers are seen as a chronic life-threatening disease rather than an acute or terminal disease. While methods used in cancer treatment increase the recovery rate, on the other hand they may cause adverse symptoms on the child and family. Fatigue is one of them which affects negatively the quality of life of the children with cancer, therefore, it is important to evaluate its effect. Fatigue should be identified and evaluated quickly pre-treatment as well as during and after, while being controlled with a multidisciplinary approach and applying appropriate nursing care.